PERAN OKI DALAM MEMPENGARUHI KEBIJAKAN LUAR NEGERI INDONESIA TERHADAP PALESTINA - Tholhah (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2025)
The role of the Organization of Islamic Cooperation (OIC) in influencing Indonesia’s foreign policy on the Palestinian issue. The background of this research is based on the importance of the Palestinian issue for Indonesia, which has consistently supported Palestinian independence. The purpose of this research is to analyze how the OIC influences the formulation and implementation of Indonesia’s foreign policy regarding Palestine, as well as to identify the mechanisms and strategies used. The research method used is a literature study, collecting and analyzing various sources such as scientific journals, books, organizational reports, and policy documents. The main findings show that the OIC provides an important platform for Indonesia to voice its support for Palestine, coordinate policies with other member countries, and provide humanitarian assistance. This study also found that Indonesia’s membership and activities in the OIC contribute to increasing international support for Palestine and influence the direction of Indonesia’s foreign policy on this issue. The study concludes that the OIC plays a crucial role in facilitating and strengthening Indonesia’s commitment to the Palestinian struggle, and recommends increased coordination and effectiveness in OIC diplomacy to support a two-state solution.